Barriers to Implementing a Public Library in Rural Areas in South Africa (Jurnal Adabiya, 2026)
This qualitative study investigates the systemic barriers hindering the realization of a public library in Kwa-Mhlanga, a rural village in Mpumalanga, South Africa. While often viewed as mere infrastructure, the library represents a vital "living room" for a community currently denied its right to information. Adopting an interpretivist paradigm, the research engaged fifty participants ranging from community members and traditional leaders to local officials to capture the lived reality of this developmental vacuum. Through semi-structured interviews and focus groups, data were analyzed thematically to uncover why the "first brick" has yet to be laid. The findings identify a critical triad of obstacles: severe financial constraints driven by unallocated budgets; bureaucratic inertia caused by fragmented mandates; and political apathy, where intellectual growth is sacrificed for more visible, revenue-generating projects. Crucially, the study reveals a painful paradox: while physical land is available and traditional leaders offer strong cultural support, these community assets are neutralized by governance failures. By providing a nuanced, pre-implementation analysis, this study moves beyond generic challenges to expose the human cost of systemic resistance. It concludes that bridging the gap between community need and institutional action requires a multi-pronged strategy: securing ring-fenced statutory funding, establishing streamlined inter-departmental task forces, and fostering sustained participatory co-design. Only through these human-centered interventions can the library transition from a stalled promise to a sustainable sanctuary for lifelong learning and community dignity.AbstrakStudi kualitatif ini menyelidiki hambatan sistemik yang menghambat terwujudnya perpustakaan umum di Kwa-Mhlanga, sebuah desa terpencil di Mpumalanga, Afrika Selatan. Meskipun sering dipandang hanya sebagai infrastruktur, perpustakaan tersebut merupakan "ruang tamu" yang vital bagi komunitas yang saat ini haknya atas informasi ditolak. Dengan mengadopsi paradigma interpretatif, penelitian ini melibatkan lima puluh partisipan—mulai dari anggota komunitas dan pemimpin tradisional hingga pejabat lokal—untuk menangkap realitas kehidupan dari kekosongan pembangunan ini. Melalui wawancara semi-terstruktur dan kelompok fokus, data dianalisis secara tematik untuk mengungkap mengapa "batu bata pertama" belum diletakkan. Temuan mengidentifikasi tiga hambatan penting: kendala keuangan yang parah akibat anggaran yang tidak dialokasikan; inersia birokrasi yang disebabkan oleh mandat yang terfragmentasi; dan apati politik, di mana pertumbuhan intelektual dikorbankan untuk proyek-proyek yang lebih terlihat dan menghasilkan pendapatan. Yang terpenting, studi ini mengungkapkan paradoks yang menyakitkan: meskipun lahan fisik tersedia dan pemimpin tradisional menawarkan dukungan budaya yang kuat, aset komunitas ini dinetralisir oleh kegagalan tata kelola. Dengan memberikan analisis pra-implementasi yang bernuansa, studi ini melampaui tantangan umum untuk mengungkap dampak kemanusiaan dari resistensi sistemik. Studi ini menyimpulkan bahwa menjembatani kesenjangan antara kebutuhan masyarakat dan tindakan kelembagaan membutuhkan strategi multi-aspek: mengamankan pendanaan resmi yang dialokasikan secara khusus, membentuk gugus tugas antar departemen yang efisien, dan mendorong perancangan bersama partisipatif yang berkelanjutan. Hanya melalui intervensi yang berpusat pada manusia inilah perpustakaan dapat bertransisi dari janji yang terhenti menjadi tempat perlindungan yang berkelanjutan untuk pembelajaran sepanjang hayat dan martabat masyarakat.